Predicting Collective Action in a Secessionist Context: Different Motives for Two Opposed Stances - Dono, Marcos; Alzate, Monica; Sabucedo, José-Manuel (Frontiers in Psychology, 2021)
Engagement in collective action is essential in the scenario of a secessionist struggle. In this scenario, two groups contend for an incompatible goal and one of them is favoured by the current status quo. Therefore, this context represents an excellent opportunity to compare the motives for participation among two groups whose situation and objectives differ drastically. We examined the motivations to participate in collective action of Catalan participants in the days leading to the independence referendum held in Catalonia (Spain) on the first of October 2017 (n = 719). As hypothesized, participation predicted by different motivations for each group. Regarding participation in the referendum, Catalan identity was the only predictor among pro-independence ranks, while those against independence showed a solidarity-based motivation. This work contributes to the literature by adapting previously researched collective action motivations to the context of a secessionist contention and providing evidence of their effect. Crucially, the motivations are different between supporters and opponents of independence, highlighting the need for examining the status and the stance on the system of groups when studying collective action.